2022
DOI: 10.20473/fmi.v58i1.29190
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Tuberculosis in Children in Taman District, Sidoarjo Regency, Indonesia

Abstract: Highlight: Pediatric tuberculosis patients profile using the medical records was determined.The most pediatric tuberculosis patients under five years have pulmonary tuberculosis.Pediatric tuberculosis patients received BCG immunization had a contact with adult tuberculosis patients histories. Abstract:The prevalence of tuberculosis (TB) in Indonesia is 391 per 100,000 population with the number of deaths around 110,000 cases in 2016. This study is descriptive research that aims to determine the profile of pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…This study found that most pediatric TB patients in Simpang Lima Gumul Hospital were male (56%). Another study in Sidoarjo also showed that pediatric TB cases were higher in males than in females (51.6%) [9]. Meanwhile, another study in Jember showed that the majority of pediatric TB patients are female (53.1%) and male (46.9%) [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that most pediatric TB patients in Simpang Lima Gumul Hospital were male (56%). Another study in Sidoarjo also showed that pediatric TB cases were higher in males than in females (51.6%) [9]. Meanwhile, another study in Jember showed that the majority of pediatric TB patients are female (53.1%) and male (46.9%) [8].…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, several studies have been published on the characteristics of pediatric TB, such as studies in Tangerang [7], Jember [8], and Sidoarjo [9]. However, there is no data from Kediri.…”
Section: Introductionmentioning
confidence: 99%
“…Penderita TB paru anak melalui 2 tahap terapi Obat Anti Tuberkulosis (OAT), yaitu 2 bulan pertama fase intensif dan 4 bulan selanjutnya fase lanjutan (8). Ketika pasien TB sudah melaksanakan terapi OAT, akan terjadi penurunan kadar Interleukin-1-beta (IL-1β), Interleukin-6 (IL-6), Tumor Necrosis Factor Alpha (TNF-α) serta menyebabkan peningkatan pembentukkan asam lemak dan penurunan lipolisis lemak di jaringan yang menghasilkan terjadinya kenaikan pada BB (9).…”
Section: Aunclassified
“…Malnutrition can result in decreased immune system thus they will be prone to TB infection. Moreover, infectious diseases may be harmful to any nutritional state 18 .…”
Section: Correlation Between Age and Prevention Of Pulmonary Tubercul...mentioning
confidence: 99%